Sanitation Assessment Report: Bashuar Village, Rajshahi, Bangladesh - Amerasinghe, Priyanie H.; Ahmed, R.; Clemett, Alexandra (2007)
This project is funded by the European Commission under its Asia Pro Eco II Program. It is undertaken by the International Water Management Institute (IWMI), Sri Lanka; COSI, Sri Lanka; the International Water and Sanitation Centre (IRC), the Netherlands; NGO Forum for Drinking Water Supply and Sanitation, Bangladesh; and the Stockholm Environment Institute (SEI), Sweden. The project pilot cities are Rajshahi City in Bangladesh and Kurunegala City in Sri Lanka.